Knockout of Hermansky-Pudlak syndrome 5 (hps5) leads to red tilapia with reduced melanophores and iridophores - Wang, Chenxu; Kocher, Thomas D.; Liu, Hao; Wen, Zilong; Yao, Jiawen; Wang, Deshou (Aquaculture, 2024)
Tilapia as an economically important fish is also an excellent model for studying pigment cell biology and body color formation. In the present study, we engineered a red tilapia by mutation of hps5 using CRISPR/Cas9 gene editing of a target site in exon 2. Disruption of HPS5 led to a significant decrease in the numbers of melanophores and iridophores, and a significant increase in xanthophores, which led to a yellowish-transparent body color in early stages (5–30 dpf, days post fertilization). Slow recovery of iridophore numbers, and increased numbers of xanthophores with shorter nearest-neighbor distances than in wild-type fish was observed at 150 dpf, which finally led to a red tilapia with reddish pigmentation in fins. The hps5⁻/⁻ mutants also showed several transparent cracks (absence of melanin, iridophores and xanthophores) in iris development. Besides, hps5 was also found to be fundamental for xanthophore development, and even the distance between each of them. Our hps5 mutants provide an excellent new model for studies of HPS5 function. Additionally, the red tilapia mutants may also have potential to serve as new germplasm for aquaculture, or function as a gene resource for genetic modification and breeding of red tilapia and the other related ornamental and food fish in aquaculture. More importantly, this study may have significant values in the area of development and evolution of pigmentation patterns of fish species.